THE RELATIONSHIP BETWEEN BUSINESS STRATEGY AND ORGANIZATIONAL CULTURE TO THE PERFORMANCE OF PHARMACEUTICAL RETAILERS IN PENINSULAR MALAYSIA: A PILOT STUDY (Journal of Technology and Operations Management, 2020)
The objective of this research is to examine the validity and reliability of the instrument for measuring the business strategy and organizational culture in pharmaceutical retailers in Peninsular Malaysia context. To date, the performance of the organizations had been studied by the researchers. However, there are still a limited number of studies done in the pharmaceutical industry, particularly among small retailers in Peninsular Malaysia. Thus, the study to examine of this area is needed and to examine the validity and reliability of the instrument is considered as the first step to facilitate further studies. The survey method was adopted for this study. A pilot test data from 30 respondents were collected and tested using factor analysis, construct validity, and reliability using SPSSV19. The results show that the instrument has a certain degree of reliability and validity and it is suitable for a study in Malaysia context. Hence, future studies can extend this finding and conduct a full scale study to establish empirical relationship between the study variables.